Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.mrgentox.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Silica coated iron oxide nanoparticles-induced cytotoxicity, genotoxicity and its underlying mechanism in human HK-2 renal proximal tubule epithelial cells

Abstract: 2019). Silica coated iron oxide nanoparticles-induced cytotoxicity, genotoxicity and its underlying mechanism in human HK-2 renal proximal tubule epithelial cells. Mutation Research/Genetic Toxicology and Environmental Mutagenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The results of this study have shown that, when treated overnight with MSNs at a concentration of 120 µg/mL, HEK293 cells presented up- or downregulated expression of certain genes and DNA degradation [ 157 ]. Královec and colleagues evaluated the cytotoxic and genotoxic potential of silica-coated iron-oxide nanoparticles (IONPs) in human HK-2 renal proximal tubule epithelial cells and reported severe disruption of the microtubule cytoskeleton structure, which resulted in antiproliferative and cytotoxic effects [ 158 ]. In this study, genotoxic effects were also described after short term exposure to 25 and 100 μg/mL of silica-coated IONPs [ 158 ].…”
Section: Biocompatibility Of Silica-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study have shown that, when treated overnight with MSNs at a concentration of 120 µg/mL, HEK293 cells presented up- or downregulated expression of certain genes and DNA degradation [ 157 ]. Královec and colleagues evaluated the cytotoxic and genotoxic potential of silica-coated iron-oxide nanoparticles (IONPs) in human HK-2 renal proximal tubule epithelial cells and reported severe disruption of the microtubule cytoskeleton structure, which resulted in antiproliferative and cytotoxic effects [ 158 ]. In this study, genotoxic effects were also described after short term exposure to 25 and 100 μg/mL of silica-coated IONPs [ 158 ].…”
Section: Biocompatibility Of Silica-based Materialsmentioning
confidence: 99%
“…Královec and colleagues evaluated the cytotoxic and genotoxic potential of silica-coated iron-oxide nanoparticles (IONPs) in human HK-2 renal proximal tubule epithelial cells and reported severe disruption of the microtubule cytoskeleton structure, which resulted in antiproliferative and cytotoxic effects [ 158 ]. In this study, genotoxic effects were also described after short term exposure to 25 and 100 μg/mL of silica-coated IONPs [ 158 ]. However, different studies have also reported very limited genotoxicity of silica nanoparticles, being this a controversial subject [ 152 , 159 ].…”
Section: Biocompatibility Of Silica-based Materialsmentioning
confidence: 99%
“…The HK-2 is a human immortalized cell line used to predict the nephrotoxicity of various xenobiotics including inorganic nanoparticles, especially on tubular proximal cells [14,23,24]. Its ability to elucidate the renal toxicity mechanisms of xenobiotics is based on the cells' expression of many enzymes and transport proteins that mediate the filtration and reabsorption in the kidneys [23].…”
Section: Discussionmentioning
confidence: 99%
“…The present study is mainly devoted to the analysis of biological effects of the final silica‐coated ε‐Fe 2 ‐ x Ga x O 3 nanoparticles on cell models in vitro. The effects of silica‐coated nanoparticles on cells have been demonstrated repeatedly in various cancer cell lines of different tissue origin, immortalized cell lines, human and mouse fibroblasts and human peripheral blood lymphocytes (Guo, Mao, Wang, Yang, & Bai, ; Královec et al, ; Lankoff et al, ; Malvindi et al, ; Yang et al, ). In spite of these numerous reports, only a very limited number of in vitro studies have examined the effect of silica‐coated particles on the cytoskeletal structures and their cellular functions (Královec et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…The effects of silica‐coated nanoparticles on cells have been demonstrated repeatedly in various cancer cell lines of different tissue origin, immortalized cell lines, human and mouse fibroblasts and human peripheral blood lymphocytes (Guo, Mao, Wang, Yang, & Bai, ; Královec et al, ; Lankoff et al, ; Malvindi et al, ; Yang et al, ). In spite of these numerous reports, only a very limited number of in vitro studies have examined the effect of silica‐coated particles on the cytoskeletal structures and their cellular functions (Královec et al, ). However, the previous studies have reported that various nanoparticles, including titania nanoparticles (Ibrahim, Schoelermann, Mustafa, & Cimpan, ), citric acid and dextran/carboxy dextran‐coated iron oxide nanoparticles (Soenen, Himmelreich, Nuytten, & De Cuyper, ; Soenen, Nuytten, De Meyer, De Smedt, & De Cuyper, ; Wu, Tan, Mao, & Zhang, ), magnetoliposomes, and citrate‐coated very small iron oxide particles (Soenen et al, , ) can affect actin and microtubule cytoskeleton as well as focal adhesion proteins and subsequently the adhesion to the extracellular matrix.…”
Section: Introductionmentioning
confidence: 97%